PENGARUH PENGGUNAAN DRAINASE VERTIKAL KERIKIL TERHADAP PENURUNAN TANAH DAN MODEL RUMAH AKIBAT LIKUIFAKSI - Setiawan, Hendra; Hilmansyah, Teguh; Arman, Arman (Universitas Bengkulu, 2022)
Liquefaction that occurred in Palu on September 28, 2018 shows that housing is the most damaged construction. Therefore, research for liquefaction mitigation devoted to residential residents becomes very necessary to be carried out, especially with simple and inexpensive mitigation methods, so that it can be affordable to most people. The selection of hollowed wood sticks as a strengthening material in this mitigation is expected to increase soil density and reduce the decrease that occurs due to liquefaction and holes made is a drainage system where at the time the pressure of pore water rises at the time of water doubling can flow in the holes that are still made or the ability of a soil in escaping water. The purpose of this study is to determine the effectiveness of the use of reinforcing logs that are perforated against soil deformation on a 1-layer variation, a 2-layer variation and a new home strengthening variation. From experimental testing obtained the percentage of effectiveness of the use of logs perforated as strengthening on several variations are as follows: For the variation of strengthening 1 layer (old house) by 13.92%, the variation of strengthening 2 layers (old house) by 26.58% and for the variation of new home strengthening as much as 54.94%.